THE SUBSTANTIATION OF THE CONCEPT OF A NEW GENERATION OF PHYSIOTHERAPEUTIC COMPLEXES - A. N. Osipov; E. G. Zaytseva; D. A. Melnichenko; M. V. Davidov; E. V. Grabtsevich (Приборы и методы измерений, 2015)
Concept of a new generation of physiotherapeutic complexes is analyzed. The requirements for the database for them are formulated. List of problems that should be addressed to create such complexes is given.